Analisis Perdagangan di Sulawesi Tenggara - Andriani Puspitaningsih; Teguh Permana; Waode Rachmasari Ariani; Surianti (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Trade is one of the crucial elements in a country's economy, playing a vital role in supporting regional and national economic growth. Through trade, a region can meet its needs and distribute its production to other areas, both domestically and internationally. Southeast Sulawesi Province, as one of the regions on the island of Sulawesi, has great potential in trade, particularly in the agricultural and industrial sectors. This province has made a significant contribution to the country's foreign exchange reserves through export and import activities. This study aims to analyze the development of trade in Southeast Sulawesi Province, focusing on the export-import performance and the region's main commodities. The method used is descriptive, utilizing secondary data obtained from the Central Statistics Agency (BPS). The results show that in 2024, Southeast Sulawesi experienced a trade surplus, where the value of exports exceeded the value of imports. The largest surplus was recorded in January 2024, amounting to 256.38 million US dollars. Three major commodities contribute significantly to the province's trade, namely cloves with a transaction value of IDR 480.74 billion, cocoa at IDR 248.74 billion, and cashew nuts at IDR 230.75 billion. These three commodities not only serve as flagship products for the local economy but also have a positive impact on the national economy. The findings of this study suggest that with proper management, the trade potential of Southeast Sulawesi can continue to grow, contributing even more to Indonesia's overall economy.